Admission rate for bronchiolitis of newborns and infants in Italian neonatal intensive care units in 2021: a survey of the Italian Society of Neonatology - Intensive Care of Early Childhood Study Group - Nunzia Decembrino; Roberta Leonardi; Tiziana Fedeli; Luana Conte; Chiara Distefano; Nicola Pozzi; Valeria Fichera; Ferdinando Spagnuolo; Camilla Gizzi; Fabio Mosca; Luigi Orfeo; Eloisa Gitto (Italian Journal of Pediatrics)
Abstract Background The shortage of Pediatric Intensive Care Unit (PICU) beds among some Italian regions is a major concern, especially during epidemics. During respiratory syncytial virus (RSV) bronchiolitis peak, Neonatal Intensive Care Units (NICU) often admit infants and toddlers requiring advanced respiratory support. We conducted a survey to quantify children hospitalized for RSV bronchiolitis in NICU in 2021 and to examine the adherence to treatment guidelines. Methods Early Childhood Intensive Care Working Group of the Italian Society of Neonatology (SIN) conducted a survey distributed to SIN Network NICUs. The modified Delphi method was used to prepare the survey; duplicate responses were excluded. Analysis evaluated percentages. Results Response rate was 67% (78/117 NICUs). Geographic distribution of responding centers was: 51% Southern-Islands, 38% North, 11% Center; 50% were Territorial Hospitals, 20% University Hospitals. Of respondents, 55% have 5–10 NICU beds; 70% routinely admit children > 44 weeks postconceptional age and > 28 days old, with a rate of < 10 toddlers/year in 50% of cases, 10–20 toddlers/year in 25% of cases and > 20 toddlers/year in 15%. In 2021, 40% of NICUs admitted < 10 bronchiolitis cases, 29% 11–20 cases. RSV was the leading cause of bronchiolitis. Reasons for NICU admission were respiratory distress syndrome (92%), feeding difficulties (58%), comorbidities (20%). High-flow oxygen (87%) and non-invasive ventilation (60%) were common respiratory supports provided; 10% of patients needed invasive ventilation. Treatment included inhaled steroids (46%), bronchodilators/systemic steroids (32%), antibiotics (40%); 60% of centers did not use sedation during NIV; 30% used midazolam, 13% dexmedetomidine, < 10% fentanyl. Conclusions Our survey highlights that during the RSV epidemic, NICUs admitted toddlers to receive advanced respiratory support unavailable in pediatric ICUs. Most of the NICUs admitted fewer than 10 toddlers per year and less than 10 bronchiolitis, posing skill challenges for medical staff. This supports SIN’s proposal to identify some “extended NICUs” in regions with limited PICU beds, to centralize toddlers after an adequate training to gain knowledge/technical skills specific of pediatric critical care. This would help to overcome the PICU beds storage. Adherence to bronchiolitis management guidelines resulted suboptimal, with frequent but unrecommended use of inhaled steroids, bronchodilators, and antibiotics.